The Social Return on Investment Methodology as A Tool for Valuation and Impact Assessment for Libraries: A Case Study. Issue 2 (3rd April 2021) - De Leon, Simon V.
ABSTRACT: Social return on investment (SROI) is an impact assessment framework that measures intangible social values used in both for-profit and non-profit types of institutions. The methodology as used by the Social Value International, consists of principles that facilitate discussions and analysis to maximize the social impact of any activity. This study sought to apply the SROI methodology as a tool for library valuation and impact assessment through a case study with the Parañaque City Public Library (PCPL) in the Philippines with data for the year 2018. The main goal is to find out if and how the library can measure its social values using the SROI method, and what are the factors that can raise the institutions' social values. Applying the methodology to the PCPL, it was found out that the resulting total SROI ratio of PCPL is 1:1.12; for every Philippine peso (PhP) 1.00 invested, the Library creates PhP 1.12 in social values. The methodology also revealed the outcomes which created the most social values for each of the stakeholders. Overall, this study shows that the SROI methodology can indeed be used in a library setting and can greatly assist libraries in programming their strategic objectives and goals.